2021
DOI: 10.1017/s0140525x21000030
|View full text |Cite
|
Sign up to set email alerts
|

Toward a productive evolutionary understanding of music

Abstract: We discuss approaches to the study of the evolution of music (sect. R1); challenges to each of the two theories of the origins of music presented in the companion target articles (sect. R2); future directions for testing them (sect. R3); and priorities for better understanding the nature of music (sect. R4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…phonological awareness) 10,11,12,13 . Given this link between spoken language and reading, and in light of theoretical frameworks positing co-evolution of rhythm- and language-related skills in humans 5,39,40,41,44 , we leveraged genomic methods to investigate the evolution of the overlap between rhythm and the reading-related aspect of language over a range of timescales (Fig. 4A).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…phonological awareness) 10,11,12,13 . Given this link between spoken language and reading, and in light of theoretical frameworks positing co-evolution of rhythm- and language-related skills in humans 5,39,40,41,44 , we leveraged genomic methods to investigate the evolution of the overlap between rhythm and the reading-related aspect of language over a range of timescales (Fig. 4A).…”
Section: Main Textmentioning
confidence: 99%
“…Our post-mvGWAS analyses enhance our understanding of the aetiology of rhythm and language (on which reading depends) by revealing intricate links across rhythm impairment, dyslexia, and various aspects of evolutionary past and neurobiological function (including gene expression in brain tissue, brain cell type-specific gene regulation, and a local genetic correlation with a tract linked to processing and production of speech and music) 5 . The evolutionary analyses aimed to provide empirical genetic data as groundwork towards understanding potential evolutionary forces acting jointly on human rhythm- and language- related skills 44,66 , revealing a candidate gene, DLAT , for future experimental investigations.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest approaches to explain the evolution of music was taken by Darwin (1871) who compared music to mating calls and suggested that music could have arisen as an adaptation through sexual selection allowing early men to compete with each other to court and win over women. However, the sexual selection hypothesis fails to explain the variety of contexts in which music takes place such as war rituals, work, mourning, and social gatherings, as well as the presence of music in children and the listening by people of all ages (Hagen and Bryant, 2003;Dissanayake, 2006;Clayton, 2009;Kirschner and Tomasello, 2010;Mehr et al, 2019Mehr et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…However, as music is largely uninformative concerning personal goals, skills, and fitness benefits of individuals (an important outcome of social bonding), it may hinder reciprocal exchange (Hagen and Bryant, 2003). In addition, Mehr et al (2021) suggested that music production is costly due to its energy and time-intensive nature. Hence, an alternative to the social bonding hypothesis has been raised where music does not cause bonding and boost cohesion directly but can reliably signal coalition strength or quality and cooperative intent or the intention to signal information on the willingness to cooperate within and between groups (Hagen and Bryant, 2003;Mehr et al, 2021).…”
Section: Introductionmentioning
confidence: 99%